Short-Term Effects of Energy-Reduced Dieting on Weight Loss, Body Composition and Metabolism in Overweight Turkish Men - Kuyumcu, Aygun; Karabudak, Efsun; Tayfur, Muhittin; Elmacioglu, Funda; Ozcelik, Ayse Ozfer; Besler, Halit Tanju (Pakistan Journal of Nutrition, 2007)
Despite ongoing health promotion, the prevalence of obesity is increasing dramatically in Turkey. To examine the short-term effects of energy-reduced dieting on body composition, weight loss and metabolism in healthy Turkish adult males. One hundred and two healthy adult males, aged 20-55 years with a BMI = 25 kg/m2 who were willing to lose weight, were studied for two months. The amount of energy in the diet, to be provided during the study was adjusted depending upon the weight loss limited to 0.5-1.0 kg/wk, normally a deficit of 2.51 MJ/day (600 kcal/day). Ankara, Turkey. After an overnight fast, sera were obtained for the measurements of glucose, total cholesterol, High Density Lipoprotein (HDL) cholesterol, triglyceride and insulin. Body composition and blood pressure measurements of participants were also determined at baseline (week 0) and weeks 4 and 8 on energy-reduced diet. The energy-reduced diet alone for two months resulted in modest weight loss (10.9%), substantial improvements in serum total cholesterol, Low Density Lipoprotein (LDL) cholesterol and in blood pressure as well as in insulin metabolism. Body fat percentage was also decreased. The data indicated that, at least in short-term, weight loss appears to profoundly enhance greater clinical benefits.